Changes in seed quality and durability of fungicides protective effect during storage period of maize seeds - F. Ghaderifar; Shahla Kheirkaman; Ebrahim Zeinali; Seyed Esmaeil Razavi; Morteza Gorzin (علوم و فناوری بذر ایران)
In order to evaluate the effect of different fungicides on storage behavior of forage maize seeds, a split plot experiment based on a completely randomized design with four replicates was conducted in seed laboratory of Gorgan University of Agricultural Sciences and Natural Resources. Treatments included fungicide (Teboconazole, Carboxin Tiram, Rovral TS, Difenoconazole and control), temperature (5˚C and 25˚C) and storage duration (12 months). Germination and cold tests were conducted to evaluate the seed quality. Also, the inhibitory effect of fungicides on the prevalence of Penicillium sp., Fusarium sp., and Alternaria sp. pathogens was investigated during storage. In this study, germination percentage of stored seeds was constant in all treatments during storage period, but the results of cold test showed that the quality of maize seeds decreased with increasing storage duration at both 5 and 25°C temperatures after some time (depending on the type of fungicide). Also, all the used fungicides (Except for Difconazole and Rovral TS at 25˚C) maintained the vigor of maize seeds during storage. The Rovral TS fungicides were more effective in inhibiting the growth and development of fungal pathogens, but according to the results of cold test, two Carboxin Tiram and Teboconazole fungicides were better in maintaining the maize seed quality during storage.